1978
DOI: 10.1073/pnas.75.9.4306
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and synthesis of a corticotropin-inhibiting peptide from human pituitary glands.

Abstract: A corticotropin-inhibiting peptide (CIP) has been isolated from human pituitary extracts. It consists of 32 amino acids with a proposed sequence identical to residues 7--38 of corticotropin (ACTH). The peptide has been synthesized by the solid-phase method. The melanotropic activity of the peptide is estimated to be 30% of the potency of ACTH. It is devoid of corticosteroidogenic activity but is able to inhibit ACTH-stimulated corticosterone production in isolated rat adrenal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…The concept that cyclic AMP is the mediator of the steroidogenic action of ACTH on the adrenal gland has been supported by previous studies (40,41 (12). This peptide is devoid of corticosteroidogenic activity and causes a 50% inhibition of ACTH-induced corticosterone production by rat adrenal cells in vitro at a molar ratio of --10,000:1 (12 proposed that a specific conformation of ACTH is necessary for receptor binding (45).…”
Section: Resultssupporting
confidence: 56%
“…The concept that cyclic AMP is the mediator of the steroidogenic action of ACTH on the adrenal gland has been supported by previous studies (40,41 (12). This peptide is devoid of corticosteroidogenic activity and causes a 50% inhibition of ACTH-induced corticosterone production by rat adrenal cells in vitro at a molar ratio of --10,000:1 (12 proposed that a specific conformation of ACTH is necessary for receptor binding (45).…”
Section: Resultssupporting
confidence: 56%
“…As expected, cortisol levels were also elevated after 1 h and returned to normal levels after 18 h of incubation with ACTH (data not shown). ACTH stimulated the StAR gene expression in the seabream head kidney preparations by binding to its specific membrane receptors, as demonstrated when 1 mM CIP, an antagonist of the ACTH receptor (Li et al 1978), effectively blocked the ACTHstimulated StAR expression in our in vitro model, without affecting the basal levels of StAR expression. The rapid increase in cortisol levels, which we observed after ACTH treatment, is in agreement with several previous studies conducted under various experimental conditions (Donaldson 1981, Nichols & Weisbart 1984, Girard et al 1998, Pottinger & Carrick 2001, Hagen et al 2006.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, some ACTH fragments not only lack activity, but act as competitive antagonists of full-length ACTH, as is the case for ACTH(7-38) (Kapas et al 1996). The latter is now known as corticotropin-inhibiting peptide (CIP) (Li et al 1978). However, ACTH(11-24) has been described as a competitive antagonist of ACTH(1-39) (Seelig et al 1971, Kapas et al 1996, whereas in another study, it has been reported to stimulate corticosterone production of ZF cells and aldosterone production of ZG cells, in addition to potentiating the effects of ACTH(1-39) (Szalay et al 1989).…”
Section: Overview Of the Acth-mc2r Complexmentioning
confidence: 99%